Negotiating the care convoys for a diverse group of older Australians living in rural communities: a large qualitative study - Petersen, Maree; Winterton, Rachel; Warburton, Jeni; Wilson, Jill (Ageing and society, 2024)
Whilst ageing in place is integral to international policy, there is less understanding of how individuals utilise formal services and informal supports in diverse rural environments to maintain their wellness and independence. Consequently, how older people negotiate their care within rural communities is subject to misconceptions. This paper draws on the convoy of care model to explore how older rural Australians negotiate their preferences and needs in the context of informal networks, availability of community resources, and the health and aged care system. The analysis draws on 60 in-depth interviews in six diverse rural communities across two Australian states. Three distinct care convoys are identified and demonstrate the interaction of multiple factors including individual preferences and needs, availability of family and community supports, and accessibility of local health and aged care services in the context of resource allocation. The findings highlight how families and communities compensate for a lack of accessible formal services. For older people without family and strong social networks, formal services are relied upon despite their inadequacy in some locales. This research has provided evidence that some Australian rural locales have limited resources resulting in challenges for older people to access home care and support. This results in many older people facing challenges to age in place. With aged care and health policy commonly designed for an urban context, our findings illustrate the importance of tailoring policy to respect the strengths and challenges existing in rural communities.